Expression of IRS1 Gene in Pregnant Women with Gestational Diabetes Mellitus, in The Third Trimester - Zainab k. Hussain; Jabbar H. Yenzeel; Hayfa H. Hassani (Iraqi Journal of Science, 2021)
To study the genetic effect of gestational diabetes mellitus by study IRS1gene expression in female with Gestational diabetes mellitus. It is characterized high level of blood glucose, especially during first trimester then increased during the 2nd and 3rd trimester of the pregnancy period. The blood samples taken from one hundred twenty healthy women and female with gestational diabetes mellitus in 3rd trimester period of pregnancy, level of fasting blood glucose (FBG) also HbA1c% measured to diagnose GDM, in addition to lipid profile (cholesterol, triglyceride, HDL, LDL, and VLDL), molecular study consist of RNA extraction and qRT- PCR for IRS1gene expression determination. The fasting blood glucose mg/dl and HbA1c% level was increased highly significantly (P<0.01) between patients and control (healthy women) in 3rd trimester stage in addition lipid profile included )serum cholesterol, serum triglyceride, LDL and VLDL( (mg/dl) but level of HDL (mg/dl) was decreased highly significantly (P<0.01) between patients and control. The result showed high significant of IRS1 expression gene in control (1.00 Â± 0.00) while in patients (0.147 Â± 0.02). The low expression of IRS1 gene was connected with gestational diabetes mellitus comparison in control (healthy women) in Iraqi female in third trimester of pregnancy